Assessment of genetically modified soybean SYHT0H2 for food and feed uses, import and processing, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐DE‐2012‐111). (20th January 2020) - ,; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: The scope of application EFSA‐GMO‐DE‐2012‐111 is for food and feed uses, import and processing of genetically modified (GM) soybean SYHT0H2 in the European Union. Soybean SYHT0H2 was developed to confer tolerance to the herbicidal active substances mesotrione and other p ‐hydroxyphenylpyruvate dioxygenase (HPPD)‐inhibiting herbicides and glufosinate ammonium. The molecular characterisation data and bioinformatic analyses do not identify issues except for sequence similarity of AvHPPD‐03 to bacterial haemolysins that was considered in food/feed safety assessment. The outcome of the comparative analysis (agronomic/phenotypic and compositional characteristics) did not need further assessment except for the changes in seed levels of α‐tocopherol and γ‐tocopherol that were assessed for food and feed relevance. The GMO Panel does not identify toxicological and allergenicity concerns for the AvHPPD‐03 and PAT proteins expressed in soybean SYHT0H2 and finds no evidence that the genetic modification would change the overall allergenicity of soybean SYHT0H2. The nutritional impact of food/feed from soybean SYHT0H2 is expected to be the same as that of food/feed from the conventional counterpart and commercial non‐GM soybean reference varieties. The GMO Panel concludes that soybean SYHT0H2 is as safe as and nutritionally equivalent to the conventional counterpart and the tested non‐GM soybean reference varieties, and no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable soybean SYHT0H2 grains into the environment, soybean SYHT0H2 would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of soybean SYHT0H2. In conclusion, the GMO Panel considers that soybean SYHT0H2, as described in this application, is as safe as its conventional counterpart and the tested non‐GM soybean reference varieties with respect to potential effects on human and animal health and the environment.